Isolated Blunt Pancreatic Trauma: A Case of Spleen Preserving Distal Pancreatectomy and One-Stage Pancreaticoduodenectomy - Molaoa, Stephen; Malongwe, Siyabonga; Mpikashe, Mvuyisi; Desemele, Yamkela; Odunze, Samuel (International Journal of Innovative Research in Medical Science, 2023)
Isolated blunt pancreatic injuries are rare. Diagnosis is often delayed due to minimal symptoms and signs. Elevated serum amylase or lipase levels on routine pre-operative laboratory investigations makes pancreatic injury highly likely. Contrast Enhanced CT scan is usually confirmatory. We are reporting on two patients who presented with blunt abdominal trauma, haemodynamically stable, and with epigastric tenderness. Pre-admission biochemical investigations revealed elevated serum amylase. CECT demonstrated Grade III and Grade IV injuries which were treated with spleen-preserving distal pancreatectomy and pancreaticoduodenectomy, respectively. Post-operatively, both developed amylase-rich fistulae which resolved on conservative management.